Testing the differences of students’ scores between two groups - Md Yusof, Zahayu; Abdullah, Suhaida; Syed Yahaya, Sharipah Soaad (AENSI Publications, 2012)
Normality and homogeneity are two assumptions that need to be fulfilled when dealing with t-test.However, these ideal conditions are rarely achieved in real world.Thus, this study proposed a robust technique that can deal with the non-normal data and variance heterogeneity.The p-value of T1 statistic that is combined with one of the popular robust scale estimators,MADn,Tn and LMSn was investigated.A simulation study was conducted to compare the robustness (Type I error) of the method with respect to its counterpart from the perspective of parametric and non parametric, i.e, the t-test and Mann-Whitney respectively. The performances of the method are demonstrated on real data on education.The findings show the favor of T1 method, especially for skewed data.